Relationship of HbA1c with Fasting Blood Glucose on Diagnostic Values and Lifestyle in Type II Diabetes Mellitus Patients - Rahayu Anggraini; Ima Nadatein; Puji Astuti (Universitas Muhammadiyah Sidoarjo, 2020)
Early diagnosis of DM (Diabetes Mellitus) is very important in reducing complications. HbA1c has been recommended as a diagnosis of diabetes in the guidelines for clinical practice as a determination of type 2 diabetes in 2011 by WHO, but is there a significant relationship between HBA1c and fasting blood glucose levels (GDP) in a person after being diagnosed with Diabetes Mellitus. In this study, the relationship between HbA1c and GDP levels was assessed through observational cross-sectional analytic based studies. The research method uses a large sample selected through the GDP test (> 125 mg / dl) of 17 people (5 men and 12 women). Statistical analysis of the test of the relationship between the HbA1c results and GDP with the Pearson Correlation, Crosstabs, and independent T test to determine the relationship of sex with GDP and HBA1c. The results of the study, there was a significant relationship between levels of GDP with HBA1c with p = 0.002, where the incidence of GDP (> 125 mg / dl) in men was 17.7% and women were 52.9%, while the results of HBA1c (> 6.5 %) in men 23.5% and women 52.9%. In conclusion, the results of HBA1c (> 6.5%) can be used for diagnosis of DM, whereas the level of GDP is only to know that people with diabetes have changed their lifestyle or not, and it is found that women are more easily change lifestyles than men, due to GDP results (<125 mg / dl) of 11.8% higher than the HBA1c yield (<6.5%) of 5.9%.